Efektivitas Aplikasi Bazkopa sebagai Media Pembayaran Zakat dan Donasi di Baznas Kota Palembang - Padil Dimas Tulus, Al; Hidayat, Hidayat; Puspita Dewi, Emi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Thesis with the title "Effectiveness of the Bazkopa Application as a Media for Zakat and Donation Payments at Baznas Palembang City" The purpose of this study was to determine the effectiveness of the Bazkopa application as a medium for paying zakat and donations at Baznas Palembang city. This research method uses quantitative research with survey techniques which are carried out by distributing questionnaires to 40 respondents. Sources of data used are primary data and secondary data, data collection techniques include observation, distribution of questionnaires/questions and interviews. Data were analyzed by Instrument Test (Validity and Reliability Test), Classical assumption test, Simple linear regression analysis, and Hypothesis Test (t test and Determination Coefficient Test) using SPSS version 25 software tools. The theory used is according to Sutrisno which states the effectiveness can be measured by looking at the extent to which the achievement of objectives is in accordance with the set targets. Meanwhile, the theory of payment media according to Turban, E., 7 & King D quoted by Agung Firmansyah which defines payment media is a payment system that supports e-commerce and provides benefits to business transactions by improving service to customers, improving cash management processes, saving money. timely and efficiently, payment transactions can be made at any time. The results of this study indicate that the effectiveness of the Bazkopa application for payment media is proven that the R Square value in the table is 0.413 which indicates that the Payment Media (Y) is influenced by the Bazkopa Application Effectiveness variable (X) of 41.3%. The results of this study indicate that the numbers are in accordance with the standard measure of effectiveness which is in accordance with the criteria of effectiveness based on the value range of 0.40 - 0.599. These results indicate that there is an effectiveness of the Bazkopa application as a medium for payment of zakat and donations at Baznas Palembang.